The relationship between attitude, skills and knowledge (ASK) with transformational leadership in oil and gas industry / Mohd Sumardi Ismail, Emisham Embong and Mohd Jonikira Jusoh - Ismail, Mohd Sumardi; Embong, Emisham; Jusoh, Mohd Jonikira (2014)
Millennium generation is the up and coming group that will have a serious impact upon the business, political, and social realms of the Malaysia. Many from millennium generation have joined the workforce and still more are to come. Transformational leadership represents the essential quality for successful management of transformational organizational changes. It is about the quality that, in fact, so-called transactional management has missed to bring to an end of the transformational cycles with efficiency. In that sense, the success in realizing transformational organizational changes means that the key people in an organization millennium generation develop sets of appropriate skills and attributes that are characteristic to so-called transformational leaders. This paper will go into the background of the desires of attitude, skills and knowledge (ASK), by all generation and demographic factors of employees in Oil and Gas Industry towards transformational leadership and how organizational change. This study employed the sampling design method to examine of attitude, skill and knowledge (ASK) towards transformational leadership by all generation or demographic factors.